The Influence of Product Quality, Packaging Design and Logo on Purchase Decisions at Kopi Pawon Nusantara Jakarta - Putri Rahmawati; Prawoto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to understand the influence of product quality, packaging design, and logo on purchase decisions at Kopi Pawon Nusantara Jakarta. The population that serves as the subject of this research is the customers at Kopi Pawon Nusantara Jakarta. The method used is accidental sampling, where a sample of 130 respondents is involved in this study. Data collection is carried out through the use of a questionnaire using a Likert scale that has been tested for validity and reliability. Data analysis is conducted using multiple linear regression analysis. To examine the overall results, hypotheses are tested using the F-test, while the T-test is used to examine individual results. The findings of this research indicate that product quality, packaging design, and logo, both partially and collectively, have a significant influence on purchase decisions.